Vietnam : Technical Assistance Report-Government Finance Statistics (June 10-14, 2019). (IMF Staff Country Reports; Country Report ;, 2020)
The main purpose of the mission was to continue TA to assist with upgrading the compilation and dissemination of fiscal data and GFS in Vietnam in line with the international standard, the Government Finance Statistics Manual 2014 (GFSM 2014).